Measuring the impact of transition on children aging out of child protective services - Chateau, Dan; Brownell, Marni; v, Joykrishna; Prior, Heather; Stevenson, Dale (International Journal of Population Data Science, 2018)
Introduction On their 18th birthday children in custody of provincial Child and Family Services (CFS) age out, and are adults in control of their own care. An additional extended transitional services program was introduced several years ago to address gaps in the provicion of, and access to, adult social services during this change. Objectives and Approach Using linked population based data from the Manitoba Population Research Data Repository, children in the custody of CFS who turned 18 during a 10 year study period were compared to children not in custody. For those in custody of CFS, we also compared individuals who participated in the extended transitional care services to those who opted out. Outcomes included use of health services and prescription drugs, social assistance, involvment with the justice system, living in social housing, and mental health outcomes. For most outcomes, the two year period prior to the 18th birthday and the two year period after were measured. Results During the study period, 4656 children in care of CFS turned 18 while in custody. There were 2811 permanent wards, of which 1663 participated in the extended transitional services program. An additional 1845 non-permanent wards also turned 18 during the study period. Permanent wards were much more likely to be long term wards (greater than six years, 65%) compared non permanent wards ( 17%). Opioid prescription rates more than doubled in the two years after their 18th birthday and were about 6 times greater than prescription rates for those not in care of CFS. Criminal accusation rates did not change after their 18th birthday, were about equal for permanent and non-permanent wards. For the majority of outcomes, the transitional services program appeared to have little impact. Conclusion/Implications Compared to children not in care of CFS, rates of most outcomes were considerably higher for wards. Not all outcomes demonstrated a significant change over the transition period. By linking data from so many different government departments, extra attention can be focused on areas likely to have the greatest impact.